Formononetin: A Pathway to Protect Neurons - Ma, Xiaoyu; Wang, Juejin (Frontiers in Integrative Neuroscience, 2022)
Formononetin is a phytoestrogen member of the flavonoid family,which has antioxidative, antihypertensive, antitumor, anti-infective, and estrogen-like pharmacological effects among others.FMN demonstrates potential in the prevention and treatment of diseases, specifically neurological diseases, such as traumatic brain injury, spinal cord injury ,ischemic stroke,cerebral ischemia-reperfusion,Alzheimer’s disease , and nerve tumor.A literature search is conducted to provide information on the signaling pathways of neuroprotection of formononetin based on the neuroprotective study.The significant neuroprotective function of FMN makes it a novel candidate for the development of drugs targeting the central nervous system.